Regionalno razvojna problematika območja ob slovensko-hrvaški meji - Pak, Mirko (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2001)
Introductory regional developmental activities in European and also in some other border areas are represented in general on some concrete examples. Analysis is following of regional developmental factors, including position, natural environment, political elements as well as general and cultural development. Most border areas near Slovene-Croatian border are not developed also due to many other factors, and further development of such areas is subject to traffic approachability, development of gravitation centres and innovations in these very areas.
Keywords: Croatia; družbeni razvoj; državne meje; Hrvatska; obmejna območja; regionalni razvoj; Slovenia; Slovenija